2019
DOI: 10.29261/pakvetj/2020.008
|View full text |Cite
|
Sign up to set email alerts
|

The Recent Update of the Situation of West Nile Fever among Equids in Egypt after Three Decades of Missing Information

Abstract: West Nile virus (WNV) is a viral disease transmitted by mosquitoes to equids and has a zoonotic impact on humans. Although the WNV infection was reported in many countries in the Middle East; a little is known about its prevalence in equine populations in Egypt for the last three decades. We have carried out serosurvey on 400 horses and 150 donkeys in five governorates located in northern Egypt. Antibodies against WNV were found in 83 samples (seroprevalence 20.7%) in horses and 19 (seroprevalence 12.7%) in do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 29 publications
2
5
1
Order By: Relevance
“…This finding was in accordance with those of previous studies, which confirmed that the risk of infection increased with the age of the dogs [20,31,32]. A popular explanation is that adult dogs remain outside for long periods and that increases their chance of contact with vectors [33][34][35][36], and that the immune response against latent infection in resistant dogs may develop in older dogs [37].…”
Section: Discussionsupporting
confidence: 92%
“…This finding was in accordance with those of previous studies, which confirmed that the risk of infection increased with the age of the dogs [20,31,32]. A popular explanation is that adult dogs remain outside for long periods and that increases their chance of contact with vectors [33][34][35][36], and that the immune response against latent infection in resistant dogs may develop in older dogs [37].…”
Section: Discussionsupporting
confidence: 92%
“…Since antibodies can be detected at all phases of anaplasmosis infection in animals, serological techniques are advantageous over microscopic investigation in many cases [ 18 ]. Serological approaches may be limited in carrier animals due to their lack of specificity, sensitivity, reproducibility, and interpretation [ 19 - 24 ]. Since competitive enzyme-linked immunosorbent assays (cELISAs) have high sensitivity and specificity, it offers more advantages than other serological tests such as the agglutination test, complement fixation test, and immunofluorescent assay [ 25 - 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In horses, the overall seroprevalence was 60.9% (n=87), which is consistent with those from previous WNF seroprevalence studies in horses in Palestine in 2014 (73%, n=210) [9], indicating that WNF is cycling in Palestine. This rate lies between the prevalence rates in endemic regions, such as South Africa (75%, n=243) [25] and Chad (97%, n=30) [26], and those detected in neighboring countries, such as Jordan (24.9%, n=253) [27] and Egypt (20.7%, n=400) [28], and in European countries, such as France (8.5%, n=432) [15]. Despite the high seroprevalence rate of WNF in horses, no clinical or laboratory diagnosis has been reported in Palestine.…”
Section: Discussionmentioning
confidence: 84%